Differences in Urinary Calculi Characteristics among the Three Main Racial Groups in KwaZulu-Natal, South Africa - Dhesigan Naidoo; Vishan Ramloutan (Journal of Renal and Hepatic Disorders)
Racial differences in the characteristics of urinary calculi are poorly described in the South African context, limiting our local understanding of urolithiasis pathology and thwarting our efforts in designing appropriate preventative interventions. We sought to investigate differences in urinary calculi characteristics among the main racial groups in KwaZulu-Natal, South Africa. We conducted a retrospective chart review of patients with urinary calculi at a quaternary hospital in KwaZulu-Natal, South Africa, during 2018–2019. We collected data on the patient’s age, sex, race (Caucasian, Asian, Black African), residence, and pre-stenting. Five study outcomes were investigated across racial groups: number of calculi, location of the calculi, size of the calculi, density of the calculi (Hounsfield Unit measurement >600), and the number of operative interventions performed. Data were analyzed with descriptive statistics, the chi-squared test, and unadjusted/adjusted logistic regression. Our study sample consisted of 147 patients (10.9% Caucasian, 55.8% Asian, and 33.3% Black African). Most patients (86.4%) were from urban areas. A higher proportion of Black Africans had urinary calculi with Hounsfield Unit measurements >600 (P = 0.002). In the logistic regression models, Black Africans had a higher probability of having urinary calculi with Hounsfield Unit measurements >600 (Unadjusted Odds Ratio: 7.17, 95% Confidence Interval: 2.00–27.80; Adjusted Odds Ratio: 18.75, 95% Confidence Interval: 3.37–157.57). Our analysis suggests that Black Africans are at higher risk of having harder urinary calculi than other race groups. This has implications for urolithiasis management and highlights the importance of primary prevention in this group. We recommend additional research to confirm our findings.